P463 COVID-19 vaccination willingness and hesitancy in patients with Inflammatory Bowel Diseases (IBD): analysis of determinants in a national survey of the Italian IBD patients' association (AMICI Onlus). (27th May 2021) - Costantino, A; Noviello, D; Conforti, F S; Aloi, M; Armuzzi, A; Bossa, F; Ficari, F; Leone, S; Manguso, F; Mocci, G; Orlando, A; Pironi, L; et al.
Abstract: Background: Vaccine hesitancy, the delay in acceptance or refusal of vaccination despite its availability, represents a threat to the diffusion and lethality of infectious diseases. COVID-19 vaccination has been recommended by national and international organizations in patients with Inflammatory Bowel Diseases (IBD). The aim of the study was to evaluate COVID-19 vaccine willingness and hesitancy in a population of Italian patients with IBD, and their determinants. Methods: In February 2021 an online questionnaire focused on COVID-19 vaccine was proposed to a representative sample of Italian IBD patients. Socio-demographic characteristics, IBD features, lifestyle, perception of COVID-19, general attitude towards vaccinations and to COVID-19 vaccines were investigated. Patients were divided into willing, hesitant and refusive towards COVID-19 vaccine. The hesitation reasons were investigated. The associations between baseline characteristics and willingness (determinants) were evaluated by calculating crude and adjusted Odds Ratio (AdjOR) with 95% confidence intervals (CI). Results: The baseline characteristics are shown below. 1252 surveys were collected. 1005 (80.3%), 222 (18.1%) and 33 (2.63 %) patients were defined as willing, hesitant and refusive, respectively. Concerns for vaccine adverse effects constituted the main reason for refusal (73.4%) (Figure). 49.1% of hesitant patients reported that presence of IBD exerted an influence on their answer. Among the patients willing to be vaccinated whenever possible, 78.2% (786) thought that their IBD represented a valid motivation to access vaccination with priority. Willingness to COVID-19 vaccine was significantly associated with adherence to previous vaccinations (AdjOR 17.6, 95% CI 11.4–27.2), male gender (1.68 95% CI 1.16–2.43), graduation degree (1.48, 95% CI 1.03–2.13), perceived higher risk of COVID-19 due to IBD (1.47, 95% CI 1.05–2.08), alcohol intake (1.69, 95% CI 1.16–2.45). Conversely, the hesitancy was significantly associated with use of complementary and alternative medicines (0.58, 95% CI 0.36–0.92). Notably, 54.5% of patients were under the impression to have a higher risk of COVID-19 and 31.8% a more severe course due to their IBD. Conclusion: Most IBD patients would accept COVID-19 vaccines, though one out of five is hesitant to date, principally due to fear of adverse events. The knowledge of determinants and reasons for COVID-19 vaccination acceptance could be a key element in developing targeted communication strategies to address vaccine hesitancy.